2017
DOI: 10.21032/jhis.2017.42.4.301
|View full text |Cite
|
Sign up to set email alerts
|

Local Spatial Autocorrelation Analysis of 3 Disease Prevalence: A Case Study of Korea

Abstract: Background: There is under-diagnosis of cardiovascular disease (CVD) in the English population, despite financial incentives to encourage general practices to register new cases. We compared the modelled (expected) and diagnosed (observed) prevalence of three cardiovascular conditions-coronary heart disease (CHD), hypertension and stroke-at local level, their geographical variation, and population and healthcare predictors which might influence diagnosis. Methods: Cross-sectional observational study in all Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…LH clusters are those where the corresponding region has low values and the surrounding area shows a high trend. At this point, it can be confirmed that HH and LL clusters each have positive spatial correlation and LH and HL clusters each have negative correlation, so they can be seen as spatially isolated regions [39].…”
Section: Lisa Analysismentioning
confidence: 82%
“…LH clusters are those where the corresponding region has low values and the surrounding area shows a high trend. At this point, it can be confirmed that HH and LL clusters each have positive spatial correlation and LH and HL clusters each have negative correlation, so they can be seen as spatially isolated regions [39].…”
Section: Lisa Analysismentioning
confidence: 82%
“…Recently, attempts to take a spatial approach are diversifying, such as using geographic information systems (GIS) for cause analysis and prevention of diseases, including cancer. 25 27 Research is being conducted to reveal spatial distribution characteristics of diseases using global and local spatial autocorrelation analysis, linear regression analysis, and geographic weighted regression analysis considering spatial heterogeneity. 18 , 25 , 28 …”
Section: Introductionmentioning
confidence: 99%